The presence of women on boards has a moderating effect on masking bribery and corruption - Krambia-Kapardis, Maria; Stylianou, Ioanna; Savva, Christos S. (My University, 2025)
This chapter presents new research into whether the presence of women on boards and/or executive management teams has a moderating effect on masking bribery and corruption through the three pillars of ESG (environment, social, and governance) disclosure. Data was extracted from the rating agency Refinitiv (LSEG) and the Compustat database for 1,466 firms in the United States from 2002 to 2023. The baseline model includes data from 456 companies. Utilizing a two-way fixed effect, unbalanced panel model, it was determined that when there is bribery, corruption or unethical behavior, (a) ESG disclosure increases, thus masking will take place, (b) the governance component of ESG remains the same, (c) the environmental and social components increase, and (d) there is less masking taking place when women serve on company boards and/or executive management teams.
Keywords: Ethics; Boards